Respostas
respondido por:
0
(b11. b12)
(b21 b22)
(b31 b32)
bij = 2i-3j
b11 = 2 . 1 - 3 . 1
b11 = 2 - 3
b11 = - 1
bij = 2i-3j
b21 = 2 . 2 - 3 . 1
b21 = 4 - 3
b21 = 1
bij = 2i-3j
b31 = 2 . 3 - 3 . 1
b31 = 6 - 3
b31 = 3
bij = 2i-3j
b12 = 2 . 1 - 3 . 2
b12 = 2 - 6
b12 = - 4
bij = 2i-3j
b22 = 2 . 2 - 3 . 2
b22 = 4 - 6
b22 = - 2
bij = 2i-3j
b32 = 2 . 3 - 3 . 2
b32 = 6 - 6
b32 = 0
(-1. -4)
(1. -2)
(3. 0)
Perguntas similares
4 anos atrás
4 anos atrás
4 anos atrás
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás